Thromboelastographic study of the snakebite-related coagulopathy in Djibouti. Issue 2 (March 2018) - Larréché, Sébastien; Jean, François-Xavier; Benois, Alain; Mayet, Aurélie; Bousquet, Aurore; Vedy, Serge; Clapson, Patrick; Dehan, Céline; Rapp, Christophe; Kaiser, Eric; Mérens, Audrey; Mion, Georges; et al.
Abstract : N/A: Hemostasis disorders are one of the major clinical conditions of snakebites and are because of mechanisms which may disrupt vessels, platelets, clotting factors and fibrinolysis. Thromboelastography (TEG) could help to understand these effects in the clinical practice. A retrospective study reports a series of patients presenting a snakebite-related coagulopathy, treated with antivenom and monitored with conventional tests and TEG in a French military treatment facility (Republic of Djibouti, East Africa) between August 2011 and September 2013. Conventional coagulation assays (platelets, prothrombin time, activated partial thromboplastin time, fibrinogen) and TEG measurements were taken on arrival and at various times during the first 72 h of hospitalization, at the discretion of the physician. The study included 14 patients (median age 28 years). Bleedings were present in five patients. All patients received antivenom. A coagulopathy was present in all patients and was detected by both conventional assays and TEG. None exhibited thrombocytopenia. Prothrombin time and fibrinogen remained abnormal for most of patients during the first 72 h. The TEG profiles of 11 patients (79%) showed incoagulability at admission ( R -time > 60 min). TEG distinguished 10 patients with a generalized clotting factor deficiency and 4 patients with an isolated fibrinogen deficiency after an initial profile of incoagulability. Hyperfibrinolysis was evident for 12 patients (86%) after Hour 6. Snake envenomations in Djibouti involve a consumption coagulopathy in conjunction with delayed hyperfibrinolysis. TEG could improve medical management of the condition and assessment of additional therapeutics associated with the antivenom.